Transformasi Organisasi pada Budaya Organisasi Polri Menuju Polri Presisi - Syahputra, Alfin Reza; Gani, Yopik; de Fretes, Yobhel Levic (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
The Indonesian National Police (INP) should become a professional, credible, accountable, transparent based on the principles of Democratic Policing. This research uses qualitative approach with case study as a research method which uses sources such as documents, books, and other related literatures. From several evaluation research show that there are lots of efforts for organisational transformation which experience failures although the INP have chosen many strategies, planning and resources as well as strong administrative commitments. Threats to the success of transformation within the organisation may emerge whether from the inside or outside. The political will in a bureaucratical field and willingness of the public which is the initiative and capability to support the INP's transformation becomes the primary key in actualising the INP that is Presisi. It is a utopia if the transformation of the INP in becoming an ideal national police comes solely from internal INP efforts. This research's recommendations are: the public must be involved actively in all processes of transformation, the need to strengthen organisational culture, moral and ethics of police, the empowerment of human resources which are based on science, and the process of transformation must be followed through continuous monitoring and evaluation.